Corporate Responsibility Gap in Environmental Violation Cases in Indonesia - Biga, Indra Ramadan (Innovative: Journal Of Social Science Research, 2024)
Law enforcement against corporations in cases of environmental damage faces various obstacles, especially in relation to the gap between civil and criminal sanctions. This study aims to examine how civil and criminal regulations are applied in environmental cases, and to explore the gap between the two and their impact on corporate accountability. Using normative legal research methods, this study analyzes relevant laws and regulations, court decisions, and legal doctrines. One of the case studies used is PT. National Sago Prima (NSP), where the Supreme Court rejected PT. NSP's appeal regarding a civil lawsuit over forest fires caused by their activities. Although PT. NSP was subject to significant civil sanctions, reaching more than IDR 1 trillion, the application of criminal sanctions was not commensurate with the magnitude of the damage that occurred. The findings of this study indicate that there is a gap in criminal law enforcement, where higher standards of proof make it difficult to prosecute corporations. On the other hand, civil law, with its lighter burden of proof, is more effective in holding corporations accountable. This study recommends harmonization between civil and criminal regulations and increasing the individual responsibility of corporate managers to strengthen the deterrent effect and ensure environmental recovery. The novelty of this research lies in the proposed integration of civil and criminal sanctions and the use of modern technology in evidence.